2013
DOI: 10.1185/03007995.2012.760444
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adverse event profile of intravenous iron sucrose and iron sucrose similar in postpartum and gynecologic operative patients

Abstract: This is the first large analysis suggesting increased adverse events due to an ISS. For our practice, the use of ISS(FRX) was discontinued owing to safety concerns outweighing the theoretical cost benefit. This study raises the question on the appropriate approval process for complex drugs and if these can be substituted without appropriate clinical testing, both for efficacy and most importantly safety, in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 22 publications
3
46
0
2
Order By: Relevance
“…Evidence from published clinical studies suggests that ISS preparations may not be equivalent to IS in either effectiveness or safety [20][21][22][23][24]. Our observations also support these findings as the effectiveness of the ISS was inferior to the original IS.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Evidence from published clinical studies suggests that ISS preparations may not be equivalent to IS in either effectiveness or safety [20][21][22][23][24]. Our observations also support these findings as the effectiveness of the ISS was inferior to the original IS.…”
Section: Discussionsupporting
confidence: 77%
“…iron therapy. A recent safety analysis showed the reporting rate of adverse events with ISSs to be nil, which is virtually impossible given the widespread, multinational use of ISS preparations [19], as well as the fact that several studies have demonstrated evidence for increased adverse events with the substitution of an ISS in clinical practice [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The fi rst was of the substitution of a follow-on iron sucrose product (Ferex, BMI Korea) for the originator (Venofer®, Vifor Pharma Ltd, Switzerland) in gynaecological patients that resulted in signifi cantly more adverse events and higher overall costs [2]. The second was of inferior therapeutic effects and increase in costs seen after substitution of the follow-on Fer Mylan for Venofer® in French renal dialysis patients [3].…”
Section: Resultsmentioning
confidence: 99%
“…The adequacy of this regulatory approval process has been questioned because therapeutic non-equivalence and non-interchangeability of authorized follow-on IV iron sucrose products have been reported [2,3]. Therefore, authorities addressed the urgent need to defi ne best practices for nanosimilar approval and post-approval pharmacovigilance to maximize the chances that such follow-on products provide patients with non-inferior safety and clinical outcomes [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…29 When compared to oral iron in pregnancy, iron stores is superior with respect to the rate of both haemoglobin increase and iron store replenishment, combined with a good safety profile. 56,64,65 Serious adverse effects are rare with IS, however minor side effects occur in patients which may associated with irritating and uncomfortable vasoactive reactions. (56) Recently there is increasing interest on alternative therapeutic options like intravenous IS and human recombinant erythropoietin (rhEPO).…”
Section: Iron Therapymentioning
confidence: 99%